Adaptive Reprogramming During Early Seed Germination Requires Temporarily Enhanced Fermentation-A Critical Role for Alternative Oxidase Regulation That Concerns Also Microbiota Effectiveness - Bharadwaj, Revuru; Noceda, Carlos; Mohanapriya, Gunasekharan; Kumar, Sarma Rajeev; Thiers, Karine Leitão Lima; Costa, José Hélio; Macedo, Elisete Santos; Kumari, Aprajita; Gupta, Kapuganti Jagadis; Srivastava, Shivani; Adholeya, Alok; Oliveira, Manuela; et al. (Frontiers in Plant Science, 2021)
Plants respond to environmental cues via adaptive cell reprogramming that affects whole plant and ecosystem functionality. Microbiota constitutes part of plant’s inner and outer environment. This Umwelt underlies steady dynamics, due to complex local and global biotic and abiotic changes. Hence, adaptive plant holobiont responses are crucial for continuous metabolic adjustment at systems levels. Plants require oxygen-dependent respiration for energy-dependent adaptive morphology, like germination, root-shoot growth, formation of adventitious, clonal and reproductive organs, fruits and seeds. Fermentative paths can help in acclimation. To our view the role of alternative oxidase (AOX) in coordinating complex metabolic and physiologic adjustments is underestimated. Cellular level of sucrose is an important sensor of environmental stress. We explored the role of exogenous sucrose and its interplay with AOX during early seed germination. We found that sucrose-dependent initiation of fermentation during the first 12 hours after imbibition (HAI) was beneficial to germination. However, parallel enhanced AOX expression was essential to control negative effects by prolonged sucrose treatment. Early down-regulated AOX activity until 12 HAI improved germination efficiency in the absence of sucrose, but suppressed early germination in its presence. Our results also suggest that seeds-inoculated arbuscular mycorrhizal fungi can buffer sucrose stress during germination to restore normal respiration more efficiently. Following this approach, we propose a simple method to identify organic seeds and low-cost on-farm perspectives for early identifying disease tolerance, predicting plant holobiont behavior and improving germination. Furthermore, our research strengthens the view that AOX can serve as powerful functional marker source for seed hologenomes.